Beneficial Effect of Statin Therapy on Arterial Stiffness. (31st March 2021) - Alidadi, Mona; Montecucco, Fabrizio; Jamialahmadi, Tannaz; Al-Rasadi, Khalid; Johnston, Thomas P.; Sahebkar, Amirhossein
Abstract : Arterial stiffness describes the increased rigidity of the arterial wall that occurs as a consequence of biological aging and several diseases. Numerous studies have demonstrated that parameters to assess arterial stiffness, especially pulse-wave velocity, are predictive of those individuals that will suffer cardiovascular morbidity and mortality. Statin therapy may be a pharmacological strategy to improve arterial elasticity. It has been shown that the positive benefits of statin therapy on cardiovascular disease is attributable not only to their lipid-lowering capacity but also to various pleiotropic effects, such as their anti-inflammatory, antiproliferative, antioxidant, and antithrombotic properties. Additionally, statins reduce endothelial dysfunction, improve vascular and myocardial remodeling, and stabilize atherosclerotic plaque. The aim of the present review was to summarize the evidence from human studies showing the effects of statins on arterial stiffness.